Drgania Swobodne Układu z Uogólnioną Charakterystyką Odcinkowo Ciągłą - Cempel, C. (Engineering Transactions, 1972)
In this paper the problem of free vibrations of a system is solved by means of the theory of distributions and the Laplace transforms method. The frequencies of vibration and the characteristics of motion are determined in the case of various types of force characteristics. In addition, a new method is developed of the impact vibration analysis based upon the preliminary constraining method.